2019
DOI: 10.1021/acs.jnatprod.8b00723
|View full text |Cite
|
Sign up to set email alerts
|

Indole Diterpenoids from an Endophytic Penicillium sp.

Abstract: A chemical investigation of the endophyte Penicillium sp. (strain ZO-R1-1), isolated from roots of the medicinal plant Zingiber officinale, yielded nine new indole diterpenoids (1–9), together with 13 known congeners (10–22). The structures of the new compounds were elucidated by 1D and 2D NMR analysis in combination with HRESIMS data. The absolute configuration of the new natural products 1, 3, and 7 was determined using the TDDFT-ECD approach and confirmed for 1 by single-crystal X-ray determination through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 70 publications
2
41
0
1
Order By: Relevance
“…The ECD curve of 4 showed strong positive Cotton effects (CEs) around 210, 275, and 325 nm (Figure 4). These data were very similar to those of shearilicine (Ariantari et al, 2019), a previously described analog bearing similar carbon skeleton as that of 4, thus leading to the assignment of the absolute configuration of 4.…”
Section: Structure Elucidation Of Compoundssupporting
confidence: 84%
See 1 more Smart Citation
“…The ECD curve of 4 showed strong positive Cotton effects (CEs) around 210, 275, and 325 nm (Figure 4). These data were very similar to those of shearilicine (Ariantari et al, 2019), a previously described analog bearing similar carbon skeleton as that of 4, thus leading to the assignment of the absolute configuration of 4.…”
Section: Structure Elucidation Of Compoundssupporting
confidence: 84%
“…HFF16 isolated from the rhizosphere soil of Cynanchum bungei Decne. in Mount Tai, East China, were investigated, which resulted in the isolation and identification of four new indole-terpenoids (1-4) named encindolene A, 18-O-methyl-encindolene A, encindolene B, and encindolene C, along with three known analogs including 7α-hydroxy-13-desoxy paxilline (5) (Peter and Christopher, 1994), 7-methoxypaxilline (6) (Ariantari et al, 2019), and paspalitrem C (7) (Dorner et al, 1984; Figure 1), which were isolated and identified. All of the compounds exhibited moderate inhibitory effects on the production of NO and proinflammatory cytokines (TNF-α and IL-6) in RAW264.7 macrophages stimulated by lipopolysaccharide (LPS).…”
Section: Introductionmentioning
confidence: 99%
“…Extrolites : Paxillin, paspalinine, shearinins ( Belofsky et al., 1995 , Houbraken et al., 2011a , Ariantari et al., 2019 ). The production of paxillin indicates a relationship to P .…”
Section: Resultsmentioning
confidence: 99%
“…Fungal secondary metabolites have always been considered an important source for drug discovery due to their diverse chemical structures and bioactivities [1]. Among them, Penicillium are recognized as important producers of structurally unusual natural products, especially of terpenes with pharmaceutical potential as illustrated with chrysogenester, an anti-inflammatory meroterpenoid-type derivative [2], shearilicine, a cytotoxic indole-diterpenoid possessing a rare carbazole unit [3,4], and the penerpenes, unusual indole-terpenoids which have shown potent protein tyrosine phosphatase inhibitory activity [5]. Insecticidal agents were also reported for penicianstinoid A, an austinoid-like meroterpenoid [6], as well as plant regulators for the dongtingnoids, diterpenoid glycosides which revealed promising seed-germination-promoting activities [7].…”
Section: Introductionmentioning
confidence: 99%
“…The EtOAc extract of the fermentation broth showed significant activity against newly hatched larvae of Helicoverpa armigera Hubner. Chemical investigation of the fungus fermentation's organic extract resulted in the isolation of four new xanthene derivatives (1)(2)(3)(4), along with one known compound 5 (Figure 1). Herein, the isolation, structure elucidation, and insecticidal activity of these compounds are described.…”
Section: Introductionmentioning
confidence: 99%